An investigation of the effect of post-injection schemes on soot reduction potential using optical diagnostics in a single-cylinder optical diesel engine. (August 2017) - Hardalupas, Yiannis; Hong, Christopher; Keramiotis, Christos; Ramaswamy, Kumara Gurubaran; Soulopoulos, Nikolaos; Taylor, Alex MKP; Touloupis, Dimitris; Vourliotakis, George; Founti, Maria A
This work employs a combination of pressure trace analysis, high-speed optical measurements and laser-based techniques for the assessment of the effects of various post-injection schemes on the soot reduction potential in an optical single-cylinder light-duty diesel engine. The engine was operated under a multiple injection scheme of two pilot and one main injection, typical of a partially premixed combustion mode, at the lower end of the load and engine speed range (ca 2.0 bar IMEP at 1200 r/min). Experiments considering the influence of the post-injection fuel amount (up to 15% of the total fuel quantity per cycle) and the post-injection timing within the expansion stroke (5, 10 and 15 CAD aTDC), under a constant total fuel mass per cycle, have been conducted. Findings were analysed via means of pressure trace and apparent rate of heat transfer analyses, as well as a series of optical diagnostic techniques, namely, high-speed flame natural luminosity imaging, CH *, C 2 * and OH * line-of-sight chemiluminescence, as well as planar laser-induced incandescence measurements at 31 and 50 CAD aTDC. The combination of post-injection fuel amount and timing has substantial effects on charge reactivity and soot oxidation potential. The analysis reveals that an amount of fuel (7% of the total fuel mass per cycle) injected more than 10 CAD after the main combustion event leads to higher levels of soot emissions, while a larger amount of fuel (15% of the total fuel mass) injected 5 CAD after the main combustion event appears to have a beneficial effect on the soot oxidation processes. Overall, results indicate that a post-injection scheme close to the main combustion phasing could reduce soot levels and improve engine performance, that is, higher IMEP levels at the same fuel consumption rates, although it could increase engine noise.